The role of genes in nurturing and shaping identity. (Journal of Universal Science Research, 2023)
The scientific article examines the role of genes in the upbringing and formation of personality. The research work of Robert Plomin is analyzed. The twin method. The foster parent method. The influence of genes on human behavior and personality formation.